Fabrication of hierarchically porous monolithic layered double hydroxide composites with tunable microcages for effective oxyanion adsorption1. Issue 70 (31st July 2015) - Tarutani, Naoki; Tokudome, Yasuaki; Fukui, Megu; Nakanishi, Kazuki; Takahashi, Masahide
<x xml:space="preserve">Abstract</x> Hierarchical porous monolithic layered double hydroxide composites with size adjusted microcages for efficient CrO42− oxyanion adsorption.